The Utility of Epworth Sleepiness Scale to Screen Moderate and Severe Obstructive Sleep Apnea Preoperatively to Predict Difficult Airway - Soori, Rashmi; D’Sa, Ivor; Hosmane, Giridhar (Journal of Health and Allied Sciences NU, 2021)
Introduction Obstructive sleep apnea (OSA) is sleep-disordered breathing characterized by repetitive episodes of partial or complete upper airway collapse in sleep leading to apnea and/or hypopnea, desaturations, sleep disruptions, and cardiovascular changes. OSA is a known cause for difficult airway, especially mask ventilation. Daytime sleepiness is one of the hallmark symptoms of OSA. So, we used the Epworth sleepiness score (ESS) in patients suspected of OSA undergoing a sleep study.Methods Overall, 44 subjects suspected to have OSA and undergoing polysomnography were included in the study. The socio-demographic details and the complaints were recorded and the Epworth sleepiness questionnaire was administered. The severity of OSA was graded as per the American Academy of Sleep Medicine using the apnea hypopnea index.Results A total of 44 patients were included in the study. Out of these, 19 were mild, 13 moderate, and 12 severe OSA cases, respectively. ESS of more than 10 showed a positive predictive value of 81.25% and specificity of 85% in screening patients with moderate and severe OSA. But the sensitivity and negative predictive value was only 54.16 and 60.71%, respectively.Conclusion ESS being a simple questionnaire can be easily used preoperatively. A score of more than 10 effectively diagnoses moderate and severe OSA, but less than 10 cannot rule out OSA
Keywords: OSA; preoperative; questionnaire